Comparison of the Effect of Glycemic Control on the Incidence of Fetal Macrosomia and Large for Gestational Age in Gestational Diabetes Mellitus Patients; A Systematic Review - Natasha Tiara Bernadette; Budi Prasetyo; Sony Wibisono; Bambang Purwanto (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Gestational diabetes mellitus (GDM) can be managed with blood glucose control management, which includes a healthy lifestyle, insulin therapy, and oral anti-diabetic drug (OAD) medications when needed. Sub-optimally or poorly managed GD Mmay lead to arisk of complications, one of which is an abnormal growth in the fetus. This study aimed to compare the effect of blood glucose control management on the incidence of fetal macrosomia and large for gestational age (LGA) births in patients with GDM. Methods: This systematic review study obtained data from formerly published studies from the Science Direct database. The article search method used the characteristics of PICO (Population, Intervention, Comparison, Outcome) and compiled using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. Conclusion: The use of medical nutrition therapy (MNT) and exercise in the therapeutic regimen, as well as routine monitoring of glycemic levels are very important to control the patient’s glycemic level. The use of metformin can increase the success of therapy due to reduced levels of LGA and macrosomia in GDM patients